Pengaruh Sukuk Sebagai Instrumen Dalam Kebijakan Fiskal Dan Kebijakan Moneter Di Indonesia - Kharisma Tri Buana Dewi; Fauzatul Laily Nisa (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
State governments provide Islamic financial instruments known as state sukuk to finance development and infrastructure projects. SBSN are state securities issued in accordance with sharia principles. SBSN shows the amount of assets in rupiah and foreign exchange. This study was conducted using a literature and qualitative approach. Overall, sukuk is an important fiscal instrument for the government in terms of financing, diversification, liquidity management, infrastructure development, debt restructuring, and Islamic financial market growth. Sukuk issuance finances the state budget and government projects, especially those related to infrastructure development.